Ecological relationships of Haemaphysalis longicornis Neumann with other tick species on wildlife hosts at cow–calf farms implementing integrated pest management in eastern Tennessee - Rebecca A. Butler; Lisa I. Muller; Dan Grove; Rebecca T. Trout Fryxell; Ala Tabor (Parasitology)
Longhorned tick (Haemaphysalis longicornis) is an invasive tick species that parasitizes a variety of vertebrate hosts and transmits pathogens affecting humans and livestock in the United States (US). Unfortunately, the behaviour of this tick at the wildlife–livestock interface is not well understood. To better understand how H. longicornis uses wildlife hosts and interacts with established tick species on farm settings we sampled small and medium wildlife seasonally for a year, using Sherman and Tomahawk traps, on three H. longicornis-infested cattle farms in eastern Tennessee. We confirmed that wildlife host body regions and coinfesting tick species were associated with the likelihood that H. longicornis would be present on a host. In addition, ticks were less likely to be present on hosts when farmer led integrated pest management strategies were adopted and the environment was modified to reduce tick populations. Results from this study can be used to target host species for on-animal management of H. longicornis by using population management strategies or acaricidal applications. Activity patterns for when established tick species, with similar predicted geographic ranges as H. longicornis, are feeding simultaneously on hosts can also be used to predict when this exotic tick species will be present. Finally, reducing tick abundance in the environment can be important for on-animal control. These results are imperative for understanding how wildlife hosts harbour H. longicornis and its interactions with established tick species. These findings are useful for selecting tick management strategies specific to H. longicornis and understanding pathogen transmission due to cofeeding.